Enhancing the Human-Machine Interface: An Analysis of Unmanned Aerial Systems (UAS) Using the System Usability Scale (SUS) - Rehder, Ivan de Souza; Sarmento, Andrew; Russo, Ana Carolina; Cardoso Junior, Moacyr Machado; Villani, Emilia (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais Estendidos do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc_estendido.2023.233145, 2023)
This study assessed the usability of an Interactive System for Unmanned Aerial Systems (UAS) using the System Usability Scale (SUS). A simulation-based experiment involved 24 pilots with varying experience levels. Results showed an average SUS score of 67.4, indicating reasonably positive usability perception. Participants without prior piloting or aeronautical experiences scored lower, while those with military or technical backgrounds scored higher. These findings highlight the importance of considering user backgrounds for effective UAS control and offer insights for usability improvements.